Pembelajaran Diferensiasi Berbasis Proyek Untuk Pengembangan Keterampilan Menulis Cerita Pendek - Lasmi, Lasmi (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to develop and implement a project-based learning (PjBL) model and differentiation in the context of short story writing at the Junior High School level. This learning model is designed to improve students’ writing skills, hone creativity, imagination, and critical and analytical thinking skills. The differentiation approach allows learning to be tailored to students’ individual interests and abilities, ensuring active participation and higher engagement. The research methods used include literature study, classroom observation, and qualitative and quantitative data analysis. The results showed that students involved in this learning model experienced asignificant improvement in the ability to write short stories. Writing projects not only help students understand narrative structure, language use, and literary techniques, but also encourage them to think critically and analytically through a process of revision and evaluation. In addition, the differentiation approach has proven effective in accommodating different student learning styles, so that each student can achieve optimal learning outcomes. Thus, this model has the potential to be applied more broadly in the educational curriculum to produce a creative, critical, and independent generation.